AN ANALYSIS OF EUPHEMISM USED BY USTAD ABDUL SOMAD IN ISLAMIC PREACH - M. Fauzy Rahman; Hermawati Syarif; Fitrawati Fitrawati (Universitas Negeri Padang, 2019)
In social communication, the using of euphemism is important to establish and maintain the relationship, because euphemism can be used to avoid unpleasant words in communication. The purpose of this study is to find out the forms and types of meaning. In this article, theory of forms and types of meaning are introduced by Warren (1992) and Leech (1981). However, there are two problems in this article. (1) what are the forms and (2) the types of meaning of euphemism used by Ustad Abdul Somad in his preach, The result shows that from 60 data, 12 forms of euphemism with loan word (30%) is the most occurred and 5 types of meaning are found with conceptual meaning (43.3%) is dominant types. The result of the study is loan word from Arabic is the dominant form because the preach talks about islam. Then, background of Ustad Abdul Somad who Studied in Egypt for his bachelor degree which used Arabic language also influence the word choice of using euphemism. Concerning the types of meaning, conceptual meaning is the highest frequencies in this study. It probably because the loan word which do not change the meaning from the source to target of language.